Downregulation of APOBEC3G by xenotropic murine leukemia-virus related virus (XMRV) in prostate cancer cells - Dey Abhinav; Mantri Chinmay; Pandhare-Dash Jui; Liu Bindong; Pratap Siddharth; Dash Chandravanu (Virology Journal, 2011)
Abstract Background Xenotropic murine leukemia virus (MLV)-related virus (XMRV) is a gammaretrovirus that was discovered in prostate cancer tissues. Recently, it has been proposed that XMRV is a laboratory contaminant and may have originated via a rare recombination event. Host restriction factor APOBEC3G (A3G) has been reported to severely restrict XMRV replication in human peripheral blood mononuclear cells. Interestingly, XMRV infects and replicates efficiently in prostate cancer cells of epithelial origin. It has been proposed that due to lack off or very low levels of A3G protein XMRV is able to productively replicate in these cells. Findings This report builds on and challenges the published data on the absence of A3G protein in prostate epithelial cells lines. We demonstrate the presence of A3G in prostate epithelial cell lines (LNCaP and DU145) by western blot and mass spectrometry. We believe the discrepancy in A3G detection is may be due to selection and sensitivity of A3G antibodies employed in the prior studies. Our results also indicate that XMRV produced from A3G expressing LNCaP cells can infect and replicate in target cells. Most importantly our data reveal downregulation of A3G in XMRV infected LNCaP and DU145 cells. Conclusions We propose that XMRV replicates efficiently in prostate epithelial cells by downregulating A3G expression. Given that XMRV lacks accessory proteins such as HIV-1 Vif that are known to counteract A3G function in human cells, our data suggest a novel mechanism by which retroviruses can counteract the antiviral effects of A3G proteins.